2008
DOI: 10.1111/j.1939-1676.2008.0090.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood Arginine Vasopressin, Adrenocorticotropin Hormone, and Cortisol Concentrations at Admission in Septic and Critically Ill Foals and their Association with Survival

Abstract: Background: Sepsis is an important cause for neonatal foal mortality. The hypothalamic-pituitary-adrenal axis (HPAA) responses to sepsis are well documented in critically ill humans, but limited data exist in foals. The purpose of this study was to evaluate the HPAA response to sepsis in foals, and to associate these endocrine changes with survival.Hypothesis: Blood concentrations of arginine vasopressin (AVP), adrenocorticotropin hormone (ACTH), and cortisol will be higher in septic foals as compared with sic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
143
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(161 citation statements)
references
References 59 publications
18
143
0
Order By: Relevance
“…In addition, if exhausted endogenous glucocorticoid synthetic capacity or adrenocortical resistance to ACTH is responsible for the lower cortisol concentrations seen in this group of foals, one would expect basal ACTH concentrations and ACTH : cortisol ratios to be higher rather than lower in hospitalized foals as compared with healthy foals. 21,22,29,30 Low ACTH concentrations in this group of foals thus suggest hypothalamic or pituitary suppression of the HPA axis, perhaps related to the effects of inflammatory cytokines stimulated by the foal's concurrent illness. [43][44][45] In contrast to previous reports, 29,30 significant differences in basal ACTH : cortisol ratios between surviving and nonsurviving hospitalized or septic foals were not identified in the present study population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, if exhausted endogenous glucocorticoid synthetic capacity or adrenocortical resistance to ACTH is responsible for the lower cortisol concentrations seen in this group of foals, one would expect basal ACTH concentrations and ACTH : cortisol ratios to be higher rather than lower in hospitalized foals as compared with healthy foals. 21,22,29,30 Low ACTH concentrations in this group of foals thus suggest hypothalamic or pituitary suppression of the HPA axis, perhaps related to the effects of inflammatory cytokines stimulated by the foal's concurrent illness. [43][44][45] In contrast to previous reports, 29,30 significant differences in basal ACTH : cortisol ratios between surviving and nonsurviving hospitalized or septic foals were not identified in the present study population.…”
Section: Discussionmentioning
confidence: 99%
“…22,[24][25][26][27][28] In addition, recent studies have identified markedly increased ACTH : cortisol ratios (increased plasma ACTH concentration with correspondingly low serum cortisol concentration) in nonsurviving septic foals as compared with both healthy foals and surviving septic foals. 29,30 Low cortisol concentration in conjunction with increased ACTH concentration suggests that failure of cortisol synthesis is primarily at the level of the adrenal gland, whereas the central portions of the HPA axis appear intact.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Possible mechanisms for these disturbances include reduced perfusion because of hypovolemia and hypotension,3, 4, 5, 6 activation of hormonal mechanisms including the renin angiotensin aldosterone system and vasopressin,7, 8, 9 tubular damage,10, 11 and perturbation of the hypothalamic–pituitary–adrenal axis 12. Plasma protein alterations might be caused by increased capillary leakage,12, 13 altered intravascular and tissue albumin distribution, imbalances between albumin synthesis and degradation14, 15 and failure of transfer of passive immunity (FTPI) 2…”
mentioning
confidence: 99%
“…The use and the clinical benefits of vasopressin in adult horses during CPR have not been determined (Muir and Hubbel 2009). The benefit of vasopressin is discussed controversial (Valverde et al 2006, Hurcombe et al 2008, Dembek et al 2014. Some authors even do not mention vasopressin when listing vasopressors (Holcombe 2006).…”
Section: Introductionmentioning
confidence: 99%